Diseases of the small bowel in chronic diarrhea: diagnosis and treatment (Medical Journal of Indonesia, 2002)
The incidence of chronic diarrhea in Asia is between 0.8-1.0%. The diseases and abnormalities according to the location, which can cause chronic diarrhea, are divided into three locations: the small bowel, the large bowel and extraintestinal. The small bowel diseases include infectious and non-infectious diseases. The infectious diseases are bacterial infections, parasitic infections etc. The non-infectious diseases include of Crohnâs disease, Celiac sprue, NSAID enteropathy, lactose intolerance, benign tumor, carcinoid tumor, carcinoma, post surgery complications, laxative etc. The approaches to diagnosis include good anamnesis, careful physical examination, supporting laboratory tests, more specialized supporting examinations including X-ray of the colon, esophagogastroduodenum follow-through, enteroclysis, ileo-colonoscopy and endoscopy on the upper portion of the digestive tract including the small intestine with biopsy for histopathology examinations. The treatment for chronic diarrhea is divided into supportive and causal therapy. (Med J Indones 2002; 11: 179-89) Keywords: small bowel, chronic diarrhea, approaches to diagnosis, treatment